Functional Connectivity Features of Resting-State Functional Magnetic Resonance Imaging May Distinguish Migraine From Tension-Type Headache - Wang, Yajuan; Wang, Yingshuang; Bu, Lihong; Wang, Shaoyang; Xie, Xinhui; Lin, Fuchun; Xiao, Zheman (Frontiers in Neuroscience, 2022)
Background: Migraineurs often exhibited abnormalities in cognition, emotion and resting-state functional connectivity (rsFC), whereas patients with tension-type headache (TTH) rarely exhibited these abnormalities. The aim of this study is to explore whether the rsFC alterations with brain regions related to cognition and emotion could be used to distinguish patients with migraine from patients with TTH. Methods: In this study, assessment of cognition, anxiety and depression using Montreal Cognitive Assessment (MoCA), Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS), and rsFC analyses were conducted in 24 healthy controls (HCs), 24 migraineurs and 24 patients with TTH. Due to their important roles in neuropsychological functions, bilateral amygdala and hippocampus were chosen as seed regions for rsFC analyses. We further assessed the accuracy of the potential rsFC alterations for distinguishing migraineurs from nonmigraineurs (including HCs and patients with TTH) by receiver operating characteristic (ROC) analysis. Associations between headache characteristics and rsFC features were calculated using multiple linear regression model. This clinical trial protocol has been registered on the Chinese Clinical Trial Registry (registry number: ChiCTR1900024307, Registered: 5 July 2019 - Retrospectively registered, http://www.chictr.org.cn/showproj.aspx?proj=40817). Results: Migraineurs exhibited lower MoCA scores (P = 0.010) and higher SAS scores (P = 0.017) than HCs. Migraineurs also showed decreased rsFC in the bilateral calcarine/cuneus, lingual gyrus (Seed: left amygdala), and bilateral calcarine/cuneus (Seed: left hippocampus) in comparison to HCs and patients with TTH. These rsFC features demonstrated significant distinguishing capabilities, and got a sensitivity of 82.6%, specificity of 81.8% with an area under the curve (AUC) of 0.868. The rsFC alterations showed significant correlation with headache frequency in migraineurs (P = 0.001, Pc = 0.020). Conclusion: The rsFC of amygdala and hippocampus with occipital lobe can be used to distinguish patients with migraine from patients with TTH.